Bridging Technology and Inclusion: Teachers’ Perceptions of Social Media for Enhancing Reading Skills in Early Grades - Humaira, Megan Asri; Sya, Mega Febriani; Effane, Anne; Laeli, Sobrul; Prasetyo, Teguh; Kafi, Muhammad Kafnun (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze teachers’ perceptions of using social media to enhance the reading skills of students with special needs in lower grades of public elementary schools. A qualitative approach with a Simple Research Design was employed. Participants included 85 teachers (Grades I–III) from 27 inclusive elementary schools across nine provinces in Indonesia. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using thematic analysis. The findings reveal four main themes: (1) increased student motivation and engagement, (2) accessibility and learning flexibility, (3) multimodal learning support, and (4) implementation challenges. The results indicate that social media has strong potential as an innovative and inclusive learning medium; however, its effectiveness depends on teachers’ perceptions and competencies. The study reinforces the integration of TPACK and Universal Design for Learning in technology-based inclusive learning. Implications highlight the need for teacher professional development and supportive educational policies